Study of visual language in Ujang’s cartoon: A case study of aku budak minang / Cao Qiang - Cao, Qiang (2016)

(untitled)
This research focused on the ―Aku Budak Minang‖, the famous comics series published in the ―Gila-Gila‖ magazine and was known as one of the best masterpieces of Ujang. Ibrahim Anon, with the pen name of Ujang, is considered to be one of the most popular cartoonists in Malaysia; His artworks produced significant impacts on both readers and contemporary cartoons in Malaysia. Raised as a Minang boy, the hometown where Ujang was born is a well-known state for its historical background as it was once ruled by the Minangkabau people from Sumatera, Indonesia since 14th century. Therefore, the inherited cultural belief is always presented in the artworks and makes Ujang special and different from other cartoonists in Malaysia. The purpose of this research will be to explore the visual language involved in Aku Budak Minang. Furthermore, the research will look closely at the Aku Budak Minang comic and to seek understanding of the minang traditions through its theme, culture, drawing style. Which relate to visual language that makes Aku Budak Minang become distinctive? In the analysis, this research is expected to determine whether Ujang‘s artworks successfully communicate the Malaysian culture to the readers through visual language, The findings of this research will indicate the social value and cultural impact during the era of 80‘s and 90‘s in Malaysia based on the point view of Ujang.